Cognition Improvement in Taekwondo Novices Over 40. Results from the SEKWONDO Study - Pons Van Dijk, Gaby; Huijts, Marjolein; Lodder, Jan (Frontiers in Aging Neuroscience, 2013)
Age-related cognitive decline is associated with increased risk of disability, dementia, and death. Recent studies suggest improvement in cognitive speed, attention, and executive functioning with physical activity. However, whether such improvements are activity specific is unclear. Therefore, we aimed to study the effect of 1 year age-adapted Taekwondo training on several cognitive functions, including reaction/motor time, information processing speed, and working and executive memory, in 24 healthy volunteers over 40. Reaction and motor time decreased with 41.2 and 18.4 s (p = 0.004, p = 0.015), respectively. Digit symbol coding task improved with a mean of 3.7 digits (p = 0.017). Digit span, letter fluency, and trail making test task-completion-time all improved, but not statistically significant. The questionnaire reported “better” reaction time in 10 and “unchanged” in 9 of the 19 study compliers. In conclusion, our data suggest that age-adapted Taekwondo training improves various aspects of cognitive function in people over 40, which may, therefore, offer a cheap, safe, and enjoyable way to mitigate age-related cognitive decline.